Sapphic Crossings : Cross-Dressing Women in Eighteenth-Century British Literature - Klein, Ula Lukszo, 1982- (Book collections on Project MUSE., 2020)
"This book considers the figure of the cross-dressing woman in eighteenth-century culture and her role in representing the possibility of lesbian and transgender embodiments"--